Sustainable business narratives in corporate sustainability reports : Discourses before and after a corporate crisis - Hakala, Niina (fi=Turun yliopisto|en=University of Turku|, 2018)
Sustainability has become a highly important topic in corporate world. Nevertheless, there is an increasing concern among many that corporations’ current sustainability agendas are drawing our attention away from the global environmental and social issues while providing companies useful legitimation tool when being criticised for unsustainable business practices. Addressing this concern, the purpose of this thesis is to critically examine the current corporate social responsibility (CSR) discourse. The objective is to make transparent the way companies build and maintain their image as sustainable organisation in their sustainability reports. To do this, the following research questions are addressed: 1) How the image of “sustainable organisation” is built in corporate sustainability reports by the use of rhetoric and how the rhetoric changes when company faces corporate crisis? 2) Which discourses form the idea of sustainable business. The objective is to increase understanding on how the idea of sustainable corporations is being constructed, and most importantly, by whom and why. Why are corporations so enthusiastically taking part in the sustainability discourse and what exactly are they aiming to sustain? This study is a qualitative case study. To study CSR as a subjective and socially constructed phenomenon, critical discourse analysis (CDA) is applied. CDA is a cross-disciplinary way to study discourses and their role in constructing the world as we understand it. The empirical material consists of two sustainability report of the chosen case company, the automotive manufacturer Volkswagen Group. The analysis is carried out through close reading of the texts. By starting from the word level rhetorical analysis, and after bordering the scope of the review to socio-political context through discourses, the study aims to reveal the multi-levelness of the concept CSR. This study offers a critique to mainstream CSR literature in which the relationship of corporate business objectives and sustainability is often presented unambiguous and conflict free. It reveals rhetorical strategies which are used to construct discourses that form the idea of sustainable business. Three dominant discourses were identified: CSR as a management tool, responsible corporate citizen and organisational learning. In addition, this study suggests that corporate scandal reinforces all three discourses. We also learn that CSR report itself works as a credible platform for company to promote its interests. The thesis therefore argues that CSR reports cannot be solely considered as objective accountability tools. Finally, the study suggests that multinational companies are not anymore just economical actors, but political as well making CSR reports also subject to political interests.